SAYYIDAH KHADIJAH AL-KUBROH AND SYARIFAH KHODIJAH AL-HINDUAN: The Idol and Inspiration of Contemporary Women from The Perspective of Sufism and Islamic Postfeminism - Dewi Masitah (Living Sufism: Journal of Sufism and Psychotherapy, 2025)
This research explores two prominent Muslim female figures, Sayyidah Khadijah al-Kubroh and Syarifah Khodijah al-Hinduan, within the context of Islamic Sufism and postfeminism. These two figures were selected not only for their historical importance in shaping Islamic civilization, but also as role models, idols, and inspirations for modern Muslim women who are currently faced with the confrontation between public and domestic duties. The purpose of this research is to analyze the examples of spiritual and social behavior provided by these two figures to contemporary Muslim women using a hermeneutic approach and the type of research is descriptive qualitative and narrative analysis. This research shows that these two figures are perfect role models for Muslim women by implementing spiritual and social values.